QUALITY, SAFETY, TEAMWORK AND PROFESSIONALISM IN GME: VALIDATION OF THE ACGME RESIDENT SURVEY. Issue 12 (18th November 2016) - Perret, Danielle; Dalal, Abhishek Kishor; Chin, Justin; Nguyen, Jeremy; Miranda-Wood, Charlene; Thompson, Coleen; Grochow, Donna; Merrill, Douglas
Abstract : Background: The ACGME Resident Survey includes questions on patient safety, teamwork, professionalism, and healthcare quality. These ACGME survey questions have not been validated. Objectives: To assess the validity of the ACGME annual survey in quality, safety, teamwork and professionalism domains by comparing ACGME to non-ACGME data, including the validated AHRQ Survey on Patient Safety Culture (AHRQCPS) and our institution's data on resident incident reporting, professionalism breaches, and quality improvement activity. Methods: 443 residents completed the ACGME Resident Survey and AHRQCPS surveys. Error/incident reports entered contemporaneously by housestaff were compared to matched ACGME items and AHRQCPS dimensions in three areas: teamwork, safety, and quality (figure 1). Results: Several ACGME Survey questions correlated, with statistical significance, with resident incident reporting (figure 2) and with the AHRQCPS (figure 3) in the Overall perception of Patient Safety dimension. The ACGME Survey item "Work in Inter-professional Teams" also correlated with the AHRQCPS teamwork dimension (figure 4). Comparisons in the areas of safety (figures 5/6) and quality (figure 7) did not produce correlations of statistical significance. Conclusions: Given the IOM findings related to healthcare quality and patient safety, the ACGME CLER program, and a national focus on teaching quality/safety in the context of GME, the ACGME has expanded its annual Resident Survey to include program assessment in the areas of quality and safety. This study is the first to demonstrate validity for several ACGME survey items in these important areas.Figure 1 Figure 2 Figure 3 Figure 4 Figure 5 Figure 6 Figure 7